Possible Involvement of Altered Arginase Activity, Arginase Type I and Type II Expressions, and Nitric Oxide Production in Occurrence of Intimal Hyperplasia in Premenopausal Human Uterine Arteries - Galina Vasileva Marinova; Renzo Ygor Loyaga-Rendon; Satoshi Obayashi; Tomoko Ishibashi; Toshiro Kubota; Masatoshi Imamura; Hiroshi Azuma (Elsevier, 2008)
In the present experiments, we tried to elucidate whether changes in arginase activity and protein expression of arginase I and II are involved in the occurrence of intimal hyperplasia in premenopausal human uterine arteries. They were obtained from thirty-four patients undergoing total abdominal hysterectomy with informed consent for the present study. All specimens were assessed histologically and the intima/media ratio (%) was evaluated as an index of the intimal hyperplasia. Thirteen patients out of 34 had histologically normal arteries (intima/media ratio = 18.1 ± 0.7%), whereas the remaining 21 patients had various degrees of intimal hyperplasia (intima/media ratio = 32.7 ± 2.3%), and these specimens were categorized as hyperplasic. Intimal hyperplasia was accompanied by impaired cyclic GMP production, enhanced overall arginase activity, and up-regulations of arginase I and II in endothelial cells and of arginase II in the smooth muscle layer. Pearson's correlation coefficient analyses revealed the close relationships among the arginase activities in endothelial cells and smooth muscle layer, the intimal /media ratio, and cyclic GMP production. These results suggest that the enhanced arginase activity and expressions of two arginase subtypes shed new light on the processes associated with the occurrence of intimal hyperplasia in premenopausal human uterine arteries. Keywords:: intimal hyperplasia, arginase I and II, cyclic GMP, nitric oxide, human uterine artery